Your statement
(n-1) + n + (n+1) = 3n +2
is false
(n-1) + n + (n+1)
= n-1+n+n+1
= 3n
I don't know what 2 2 2 2 is supposed to mean.
prove that
2 2 2 2
(n-1) + n + (n+1) = 3n +2
2 answers
Looks like an attempt at exponents, not counting on html formatting:
(n-1)^2 + n^2 + (n+1)^2 = 3n^2 + 2
Now come on, guy. Just expand the expressions, and the +2n and -2n cancel out, and the +1 and +1 add up to 2.
Where do you have trouble here?
(n-1)^2 + n^2 + (n+1)^2 = 3n^2 + 2
Now come on, guy. Just expand the expressions, and the +2n and -2n cancel out, and the +1 and +1 add up to 2.
Where do you have trouble here?